A Competitive Positioning Management Information System - MAHESHWARI, NIKHIL (The journal of contemporary issues in business and government, 2021)
Information system is an integrated range of data collection, storage and treatment components, as well as for the provision of information, cards and digital products. Business organizations, for the execution and control of their activities, employ computer technology to communicate with clients and vendors and operate on the market depend on information systems. The exponential proliferation of emerging technology has created a global village for companies, thus creating a volatile world requiring companies to be agile, responsive and resilient to survival. The growing rate of technological progress, combined with a tumultuous socio-political global climate, has created opportunities and challenges for companies especially in the manufacturing sector in terms of productivity and sustainability. Manufacturers in the developed world are trying to build knowledge-based and hands-on information management systems that will allow them to compete competitively on the global market. This article discusses the application of strategic positioning corporate information systems, using a case analysis from a manufacturing business based in sub-Saharan Africa. Their results indicate the need for an integrated management information system that integrates science, knowledge management, and organizational performance and ability-based management activities.